Seeing is Deceiving: The Effects of Stimulus Adaptation on Perceptual Error in the Ebbinghaus Illusion - Kersten, Courtney G. (My University, 2006)
Although visual illusions have been used extensively to explore the mechanisms subserving perception and action, controversy exists regarding the extent to which illusions may differentially affect the perceptual and motor systems. In part, this is because it is often difficult to accurately assess the perceptual influence of illusory stimuli since participants are usually asked only to report binary size decisions (bigger or smaller) of an illusory stimulus relative to a control figure. Questions of relative size or the direction of misperception remain unanswered. In this thesis, 10 experiments, comprising eight separate studies, were conducted to address these issues. In Experiment 1, a software tool was developed that allowed participants to size-match a target to a Control figure (Experiment 1a), as well as both the Large (Experiment 1b) and Small Annuli (Experiment 1c) Ebbinghaus Illusion stimuli. These experiments provided an accurate percentage of misperception score when each of the three conditions was presented in isolation. Results from Experiment 2, however, suggest that when each of the three conditions are presented in a random and repeated stimulus array, a degree of perceptual adaptation occurs in which illusory effects are biased in the direction of the large annuli stimulus. Experiments 3-8 provided evidence to suggest that the degree of motor involvement (Experiment 3), number of illusory stimuli present (Experiments 4 and 5), direction of attention (Experiment 6) and visual field laterality (Experiments 7 and 8) have minimal influence on the adaptation effects observed in Experiment 2.
Page 193 is included twice. Numbered the same, but are different pages.
Keywords: stimulus adaptation, perceptual error, Ebbinghaus illusion, seeing, deceiving